Sukin Skincare Product Advertisement in Social Media: A Multimodal Analysis - Grace Widya Panggabean; T. Thyrhaya Zein; Dian Marisha Putri (Talenta Publisher, 2022)
This research investigates the level modality of Sukin skincare product advertisement in social media through the descriptive qualitative method. Kress and Van Leeuwen propose the theories supporting this thesis. The primary data sources in this thesis were ten visual advertisements. The steps passed in this analysis are selecting ten visual images, identifying the visual elements of the ten advertisements, categorizing the visual elements into visual contact, social distance, perspectives, modality, and putting them in the table. The result of this thesis shows there are 5 of demand images, 15 of offer images, 12 of far social distance, 7 of close personal distance, 1 of close social distance, 8 of high modality, 2 of low modality, 20 of frontal angle, and 20 of eye level. Thus, it can be concluded that far social distance is dominant, indicating that the company intends to show truthfulness and credibility in convincing the viewer to try the products. It is also demonstrated that the multimodal visual element plays a pivotal role in directing the advertisement's message towards the audience